Reform in tertiary education. - Henchey, Norman (1990)
Attempts to clarify some of the concepts of tertiary education and reform. Discusses the objectives of, and identifies four major themes in, the reform of tertiary education, viz. expansion of tertiary education, diversification of institutions and programmes, development of the non-univeristy sector, and issues related to the investment in human resource development. Believes these issues have implications for Eastern Caribbean states to how reform is approached.